Global perspectives on the provision of diabetic retinopathy screening and treatment: Survey of health care professionals in 41 countries. (September 2018) - Cavan, D.; Makaroff, L.E.; da Rocha Fernandes, J.; Karuranga, S.; Sylvanowicz, M.; Conlon, J.; Chaney, D.; Malhi, A.; Barratt, J.
Abstract: Aim: To assess the level of awareness and provision of screening and treatment for Diabetic Eye Disease (DED) comprising Diabetic Retinopathy (DR) and Diabetic Macular Edema (DME) among health care professionals. Methods: The study was conducted in two phases. The first phase consisted of a qualitative study, based on semi-structured face-to-face and telephone interviews in 8 countries. The second phase used a quantitative approach utilising online surveys in 41 countries. The survey for health care professionals comprised of 43 questions covering provider information, practice characteristics, management of adults with diabetes and specific information from ophthalmologists on screening and treatments for DR. Results: There were 2329 health care professionals who participated in the online survey. More than one third of diabetes specialists surveyed reported that they did not discuss eye care with their diabetes patients. Nearly two-thirds of all health care professionals surveyed reported that they had written information about diabetes for patients available in their practice. Only one in five (22%, n = 58) primary care providers reported they had material that contained sufficient information on eye complications, and 37% (n = 252) of ophthalmologists reported that they had sufficient information on eye complications. Sixty-five percent (n = 378) of ophthalmologists reported that most of their patients presented when visual problems had already occurred. Six percent (n = 36) stated that most of their patients presented when it was already too late for effective treatment. The most substantial barriers to eye health mentioned by health care professionals responding to the survey were: a patients' lack of knowledge and/or awareness about eye complications (43%), followed by lack of importance given to eye examinations by patients (33%), and the high cost of care (32%). Ophthalmologists also reported late screening (66%), and lack of patient education materials (55%) as obstacles for improving eye health outcomes. Conclusion: Health care professionals need to be appropriately supported and trained so they can provide adults with diabetes with information about the risks of DR, support them in reducing their risk, and advocate for the provision of affordable DR screening and treatment as required.